De novo assembly of a chromosome-level reference genome of the ornamental butterfly Sericinus montelus based on nanopore sequencing and Hi-C analysis - Li, Jingjing; Wang, Haiyan; Zhu, Jianqing; Yang, Qi; Luan, Yang; Shi, Leming; Molina-Mora, José Arturo; Zheng, Yuanting (Frontiers in Genetics, 2023)
Sericinus montelus (Lepidoptera, Papilionidae, Parnassiinae) is a high-value ornamental species widely distributed in Northern and Central China, Japan, Korea, and Russia. The larva stage of this species is famous for its feeding on the host Aristolochia plants that naturally contain aristolochic acids (AAs) known to result in a risk of cancer development in mammals. However, the genetic adaptation of S. montelus to AA tolerance has not yet been well understood because of the limited genetic information of this species. Here, we present a chromosome-level genome of S. montelus using the Oxford Nanopore long reads sequencing, Illumina short reads sequencing, and Hi-C technologies. The final assembly is composed of 581.44 Mb and 99.98% of bases can be anchored onto 30 chromosomes. The N50 of contigs and scaffolds are 5.74 Mb and 19.12 Mb, respectively. Out of the whole genome, about 48.86% is suggested to be composed of repeat elements, and 13,720 protein-coding genes were identified. Phylogenetic analysis shows that S. montelus was separated from the common ancestor of swallowtails 69.52 million years ago. Compared with relative species, S. montelus shows a significant expansion of P450 gene family members, and positive selections on eloa, heatr1, and aph1a may result in the AA tolerance for S. montelus larva. The de novo assembly of a high-quality genome of S. montelus provides an important insect model organism resource for the study of evolution, genome genetics, and toxicology on AA tolerance in the future.